ACT-based training for primary care professionals: a pre-experimental study - Salati, Leonardo Romeira; Freitas, Breno Irigoyen de; Soares, Jennifer Mendes (Perspectivas em Análise do Comportamento, 2025)
Primary Care constitutes the principal gateway to Brazil’s Unified Health System and plays a pivotal role in meeting mental health demands. Nonetheless, several barriers hinder the effectiveness of care delivery. This study aimed to evaluate the impact of a semistructured, experiential training grounded in the principles of Acceptance and Commitment T herapy, administered to healthcare professionals operating within the Primary Care network of a municipality in Rio Grande do Sul. A quantitative, pre-experimental intervention design was employed, incorporating pre-test and post-test assessments without a control group. Eleven Primary Care professionals participated (mean age = 45.9 years; 90.9% female; 81.8% working as Community Health Agents). Post-training analyses revealed positive changes in mean scores for psychological flexibility, psychological distress, and willingness to provide mental health care. Additionally, the intervention enhanced clarity of personal values and increased work-related psychological flexibility, factors that are likely associated with the observed rise in mental health care engagement. These preliminary findings support the feasibility and positively oriented outcomes of this training intervention and offer a foundation for future rigorous investigations.